Keselamatan dalam perumahan komuniti berpagar. Kajian kes – Apartment Prima dan Taman Kristal 2, Sepang Selangor - Mohd. Noor, Norazman (2010)
The development of gated community projects (PKB) has become the latest housing development trend in Selangor. The local people who are keen in purchasing or renting such properties are willing to leave the conventional housing estate that has been the norm to retreat to an enclave secured behind high walls and imposing fences. People start seeking the gated community scheme that can provide better security. However, gated community is not impenetrable. Fencing and walls are sometimes too low and enough for someone to climb in. The 24 hour security patrols also may not cover the whole community at the same time due to the limit in amount. The aim of this study was to assess effectiveness security features in crime prevention. Writer concentrate study cover population profile, perception on gated community development, crime prevention and crime rate in study area. Information of the study obtained through both primary and secondary source. Primary data are collected through surveys involving 30 respondents (15 from Apartment Prima and 15 from Taman Kristal 2) in this area. From view of this research, gated community scheme was assumed as a secured living, but it still have their weakness, which based on criminal cases happened in this particular research area.